DEVELOPING SKILLS OF COMPOSING A PARAGRAPH AS A STRUCTURAL ELEMENT OF AN ENGLISH-LANGUAGE WRITTEN TEXT WHEN TEACHING WRITING TO LANGUAGE STUDENTS - Nataliya Odegova (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
In the article the author explores the concept of paragraph as a means of logically structuring a written text; outlines the principles of arranging a body paragraph; examines the functions of a topic sentence, supporting sentences and a concluding one; identifies the specific skills of writing a paragraph; offers a set of activities aimed at mastering the specified skills in the context of developing English-language competence in writing. The suggested sequence of activities presupposes step-by-step practice in writing sentences of the types mentioned with the gradual transition to composing complete paragraphs. Special attention is paid to pair and group work for the purpose of lessening the adverse effects of writing-related stress.